External debt statistics : guide for compilers and users - International Monetary Fund. (Washington, DC : International Monetary Fund, 2003)
Contains updated global standards for the compilation, reporting, and analytical use of external debt statistics.
Includes index.
Includes bibliographical references (p. 294-296)
oif 07/05/2018
Ref.
Keywords: Debts, External